Surgical management in hepatocellular carcinoma with portal vein tumour thrombosis: is this the end of the road or a chance to expand the criteria for resectability? - Benatatos, Nikolaos; Papadopoulou, Iliana; Assimakopoulos, Stelios; Mulita, Francesk; Iliopoulos, Evangelos; Germanos, Stylianos; Vailas, Michail; Kalogeropoulou, Christina; Kitrou, Panagiotis; Maroulis, Ioannis (Gastroenterology Review/Przegląd Gastroenterologiczny, 2022)
Portal vein thrombosis is a common complication associated with malignancies such as hepatocellular carcinoma, with a dismal and negative impact on prognosis. A thorough literature search in Pubmed and Google Scholar, under the terms ‘hepatocellular carcinoma AND portal vein thrombosis’, regarding the surgical management of portal vein thrombosis was conducted by the authors, and the associated results are presented in this narrative review. Precise classification of portal vein thrombosis and identification of subgroups of patients that will benefit from surgery is of paramount importance. Evolution of novel surgical techniques in liver resection and associated low morbidity and mortality rates in specialized hepatobiliary centres worldwide have been linked with promising results from the adoption of surgical management in these patients, when compared to systemic chemotherapy or arterial chemoembolization management that has traditionally been followed in such cases.